Ornamental Variety of Tombs of Sigam Kings in 1855-1900 in the Wetland Area of Sigam Sea Island, Kotabaru Regency - Yahya, Daud; Efendi, Rusdi (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
History and culture have begun to be fulfilled by the younger generation, it takes effort to map history and concrete explanatory evidence of each heritage site from the past. Kotabaru Regency is one of the centers of study of this research because many historical relics were found in the form of tombs from the Sigam Kingdom that received less attention from related agencies. Therefore, deeper research is needed so that it can be an evaluation material for future policies and strategies. This study aims to find out how the shape of the tomb (typology) and the variety of ornamental tombs of the kings of Sigam in 1855-1900. The research method uses historical methods: (1) heuristics, (2) source criticism, (3) interpretation, (4) historiography. The results of this study are as follows: This cemetery is a complex of tombs of kings, Kingdoms, Sea Island and their relatives. The King of Pulau Laut who is buried in this complex there are three people, namely Prince Jaya Sumitra bin Pangeran Muhammad Nafis, Prince Abdul Kadir bin Pangeran Muhammad Nafis, and Pangeran Brangta Kesuma bin Pangeran Abdul Kadir. The tombstones of the kings are currently covered in yellow cloth by the surrounding community.